Design and fabrication technologies for microfluidic sensors - Nordin, Anis Nurashikin; Abd Manaf, Asrulnizam (Elsevier, 2023)
Microfluidic devices have shown tremendous promise as miniature lab-on-a-chip platforms that are capable of performing rapid and efficient experiments on small sample volumes. These devices, also known as micro-total analysis systems, are widely popular since they reduce the risk of contamination, cost less per analysis, allow automation and reduction of tedious operations, provide enhanced sensitivity and specificity, and have better reliability than conventional laboratory-based tests. Leveraging on the technologies used in semiconductor manufacturing, lab-on-chips can be fabricated as a miniaturized analytical technology for both biomedical and chemical applications. This chapter explains the design and modeling of microfluidic platforms for sensing, mixing, and droplet generation. Fundamental design principles such as laminar and electrokinetic flow are explained first, followed by different modeling techniques for these devices. Comparison between conventional fabrication methods for fluidic devices using polydimethylsiloxane and current trends of manufacturing microfluidic devices using paper and plastics is detailed next. Paper- and plastic-based fluidics have become extremely popular in recent years due to their cost-effective methods and ease of fabrication in low-resource settings. Usage of microfluidics in the real world is also described, for both biosensing and environmental applications. For biosensing, the usage of fluidics in glucose sensing is detailed, while for environmental applications, an example of a microfluidic device used for heavy metal ion detection is illustrated. Finally, the chapter concludes with future outlooks for microfluidic platforms.